Unlocking run-of-river hydropower potential in semi-arid regions through modular turbines - Imane El Kasimi; Moulay Driss Hasnaoui; Driss Khomsi (International Journal of Renewable Energy Development, 2026)
The growing global demand for renewable energy has increased the need to diversify electricity systems toward low-impact sources. In this context, run-of-river hydropower plants are increasingly recognized as promising options, as they can generate electricity with relatively limited environmental and social disruption. However, their potential in arid and semi-arid regions remains underexplored, especially under highly variable hydrological conditions. In this context, this study assesses the technical hydropower potential of the semi-arid Bouregreg watershed in Morocco using a distributed run-of-river scheme. The Soil and Water Assessment Tool model was used to simulate streamflow and establish power-duration curves throughout the watershed. These curves were then used to estimate the technical potential based on a modular turbine system consisting of an optimal number of identical Crossflow turbines operating in parallel. The calculations incorporated technical and environmental constraints and were complemented by a preliminary cost assessment. The potential was also evaluated under typical, extreme dry, and extreme wet hydrological conditions. The results indicate a total hydropower potential of 34.3 MW under typical conditions, increasing to 89 MW under wet conditions and decreasing to 12.5 MW under dry conditions. Although the cost analysis revealed values slightly higher than reported average small-hydropower costs, some sites remained within reasonable cost ranges, particularly in the Grou subwatershed, where the estimated annual energy production could potentially cover approximately 58% of its population’s annual electricity demand under normal hydrological conditions. These findings highlight the existence of underexploited potential of run-of-river systems in semi-arid basins and provide a preliminary framework for identifying viable hydropower opportunities.